Natural history of primary syphilis: clinical and serological aspects of chancre concurrent with Follmann’s balanitis - Veasey, John Verrinder; Munhoz, Sandy Daniele; Francisco, Laura Rodrigues Moda (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Primary syphilis is classically represented by a hard chancre, but other rare forms such as Follmann’s balanitis are occasionally described. Objective: To show an iconography of the clinical presentations of the classic hard chancre and Follmann’s balanitis, in parallel with the serological results in the course of diagnosis and treatment. Methods: Descriptive case report of a patient of an outpatient clinic for sexually transmitted infections in a tertiary hospital in the city of São Paulo, SP, Brazil. Conclusion: Syphilis lesions acquire different clinical expressions according to the natural evolution of the disease. Recognizing these presentations, as well as knowing how to interpret the serological results, is essential for the diagnosis and adequate treatment of the infection.